1999
DOI: 10.1093/ajcp/112.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B-Cell Lymphoma: A Report of Five Cases Initially Diagnosed by Bone Marrow Biopsy

Abstract: A b s t r a c tWe report 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 4 publications
1
44
1
Order By: Relevance
“…19,28 However, subsequent studies indicate that this disease involves the marrow with greater frequency than originally suggested. 20,25 In our patients with diffuse splenic involvement by LBCL, there was a predominant, but not exclusive intrasinusoidal pattern of marrow infiltration. Detection of marrow involvement by LBCL in our cases was greatly facilitated by anti-CD20 immunoperoxidase staining as morphologic clues to the diagnosis were obscured both by the pattern of marrow involvement and the associated prominent erythroid hyperplasia.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…19,28 However, subsequent studies indicate that this disease involves the marrow with greater frequency than originally suggested. 20,25 In our patients with diffuse splenic involvement by LBCL, there was a predominant, but not exclusive intrasinusoidal pattern of marrow infiltration. Detection of marrow involvement by LBCL in our cases was greatly facilitated by anti-CD20 immunoperoxidase staining as morphologic clues to the diagnosis were obscured both by the pattern of marrow involvement and the associated prominent erythroid hyperplasia.…”
Section: Discussionmentioning
confidence: 57%
“…4 An intrasinusoidal pattern of marrow infiltration has been described in intravascular LBCL as well as in a number of other lymphoproliferative disorders including splenic marginal zone B-cell lymphoma, hepatosplenic T-cell lymphoma, and T-cell large granular lymphocytic leukemia. [21][22][23][24][25][26][27] These latter disorders share as a unifying feature prominent splenic involvement. It is recognized that morphologic detection of intrasinusoidal marrow involvement by these disorders is exceedingly difficult.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, it is not clear what proportion of intravascular large B-cell lymphomas lack these adhesions molecules, nor whether additional mechanisms may be responsible for the intravascular location of these neoplasms. In addition, although other cases of CD5-positive intravascular large B-cell lymphoma have been reported in the literature, [25][26][27] it remains unclear whether there is any mechanistic relationship between CD5 coexpression and intravascular localization in these lymphomas. Although one study of intravascular lymphoma identified bone marrow involvement in four of five cases, and peripheral blood involvement in all five cases, 25 we have not been able to detect the neoplastic cells in the peripheral blood or bone marrow by flow cytometry in case 2, even though this patient has been extensively followed by our institution because of the recurrent lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although other cases of CD5-positive intravascular large B-cell lymphoma have been reported in the literature, [25][26][27] it remains unclear whether there is any mechanistic relationship between CD5 coexpression and intravascular localization in these lymphomas. Although one study of intravascular lymphoma identified bone marrow involvement in four of five cases, and peripheral blood involvement in all five cases, 25 we have not been able to detect the neoplastic cells in the peripheral blood or bone marrow by flow cytometry in case 2, even though this patient has been extensively followed by our institution because of the recurrent lesion. The staging bone marrow in case 1 was reportedly negative by morphology; however, to our knowledge, neither that patient's blood nor bone marrow was ever evaluated by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Estalilla et al 6 reported five cases, initially diagnosed by bone marrow biopsy, and speculated that involvement of bone marrow and peripheral blood might be more common than has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%